Augmented Reality (AR) pada Geogebra Meningkatkan Kemampuan Spasial dan Pemecahan Masalah Matematis pada Materi Dimensi Tiga - Herman Herman; Alianus Zalukhu; Doni Berkat Tabah Hulu; Nesti Surya Astuti Zebua; Efron Manik; Adi S Situmorang (Departement of Mathematics Education, 2023)
One of the factors that can improve learning outcomes is the use of learning media. Today, there are many choices of media to be used in the teaching and learning process. The use of ICT-based media is one option that is currently being widely used. One technology that can be taken into account is the use of Augmented Reality (AR) media. Augmented Reality (AR) is a technology that integrates two-dimensional or three-dimensional objects into a real environment. The use of AR in learning can make learning more interactive. The purpose of this study is to describe Augmented Reality (AR) learning media in learning. The method used in this study is the method of literature review or literature study as a source of data. After tracing the data, it was found that Augmented Reality (AR) had a positive effect on spatial abilities and mathematical problem solving abilities. Therefore, the use of this media can be an option for educators in conveying materials related to geometry.